Pengaruh Perceived Organizational Support Dan Organizational Citizenship Behavior Terhadap Task Performance (Studi Kasus Pada Divisi HRD PT. ASTRA DAIHATSU SUNTER) - Sulastriningsih, Dewi (LPPM Universitas BSI, 2014)
ABSTRACTPerceived Organizational Support (Kaufman and Stamper) can be defined as beliefs of workerâs seriousness level of organization in participate a boost to them related to the development of the potential and capacity to achieve higher performance. Perceptions of organizational support as the employeesâ beliefs that organization regard and reward their contributions to the success of the organization. Organizational Citizenship Behavior often defined as the individuals behaviour who have the freedom to choose indirectly or explicitly which approved by the reward system, and contribute to the effective and effisience functions of organization (Organ et al,). According to Borman and Motowidlo et. Al. Task performance is the activitiy that directly involve the core tasks fulfillment or support the achievement of the tasks involved organization